Residual effects of biochar on growth, photosynthesis and cadmium uptake in rice (Oryza sativa L.) under Cd stress with different water conditions. (15th January 2018) - Rizwan, Muhammad; Ali, Shafaqat; Abbas, Tahir; Adrees, Muhammad; Zia-ur-Rehman, Muhammad; Ibrahim, Muhammad; Abbas, Farhat; Qayyum, Muhammad Farooq; Nawaz, Rab
Abstract: Soil cadmium (Cd) contamination and drought stress are among the main issues hindering global food security. Biochar has been used to reduce metal uptake by plants and water stress mitigation, but long-term residual effects of biochar under Cd stress at different moisture levels needs to be investigated. A following rice ( Oryza sativa L.) was grown after wheat on Cd-contaminated soil amended with different levels of biochar (0, 3.0, and 5.0%, w/w). Thirty five days old plants were irrigated with three moisture levels including zero drought as a control (1–2 cm water layer on soil), mild drought (MD, 50% of soil water holding capacity, WHC), and severe drought (SD, 35% of soil WHC) for an accompanying 35 days. Plant height, biomass and photosynthesis were reduced whereas oxidative stress increased under MD and SD than control in un-amended soil while opposite trends were observed in plants grown in biochar amended soil. At the same biochar addition, Cd concentrations in seedlings were lower in continuous flooding than MD and SD treatments. The biochar supply reduced the bioavailable Cd in the soil whereas increased the soil EC and pH than the control treatment. In conclusion, continuous flooding plus residual biochar can be strategized in mitigating Cd-contamination in paddy soils and decreased Cd concentrations in rice which may reduce the potential risks to humans. Highlights: Continuous flooding immobilized cadmium (Cd) in soil by biochar. Biochar increased plant growth and reduced oxidative stress. Biochar increased soil pH and reduced bioavailable Cd in the soil.